INFLUENCE OF CARBON NANOPARTICLES ON HISTOMORPHOLOGICAL DIGESTIVE (Experimental biology, 2016)
Ehnterosorbentov significant features is the fact that they are purified and disinfected with gastrointestinal tract by the intestinal mucosa it may inhibit the metabolism products entering the bloodstream. To investigate the workings on the organism enterosorbent albino rats were studied organs of the digestive system: the esophagus and stomach. Known that on admission the organism toxic substances in the with food target organs is first of all digestive organs. Part toxins accumulated by in the organism, especially in organs with high levels metabolism (e.g., liver), and is excreted through the kidneys and outwards skin. Appropriate reactions are observed with cells and tissues of the in the liver, stomach, kidney et al. bodies. Selection for the study digestive organs due to the fact that they among the first react to the ingress of toxic of substances with food, and thus, can serve as indicators of toxicity of different of food additives, medicaments, and other substances.
Keywords: nanoenterosorbent "Ingo-2"; the digestive system; esophagus; stomach; morphology; physiology; mucous membrane; rat epithelium; basal layer